Virtuoses ambivalents - Graham Jones (Ateliers d'Anthropologie)
This article compares the approaches of two different classes of magicians: entertainers who use illusion to entertain and apostles of Christianity who use illusion to evangelize. Instead of presenting their illusions as a demonstration of skill, these gospel magicians use them as a way of imaging figuratively the stories and lessons that carry a Christian message. Emphatically denying supernatural powers and scrupulously avoiding any effects that resemble biblical miracles, they take care to present their performances as clever tricks clearly designed to entertain, educate and galvanize. Like their secular counterparts, gospel magicians propose tricks full of virtuosity. But while secular magicians celebrate virtuosity as a central element of magic, gospel magicians minimize its role.